Análise dos indicadores do sistema de avaliação da pós-graduação stricto sensu no Brasil: um estudo multicasos nos programas de Engenharia de Produção - Flores, Raquel Dalvit (2014)
In a world, where the market becomes increasingly dynamic and competitive, it is essential to invest in education to ensure that development and progress. Programs of graduate studies aim to contribute efficiently to the production and dissemination of knowledge and hence the scientific and technological autonomy of the country. Coordination of Improvement of Higher Education Personnel (CAPES) in Brazil is the responsible body for the training of human resources, control, evaluation and management of programs and graduate studies. The present study had as main aim to carry out a quality and quantitate analysis of the indicators of CAPES evaluation system in the area of Production Engineering. The methodology of this study, this research is characterized as an approach for being qualitative and quantitative exploratory and descriptive, which was adopted different methods and techniques in each phase of the study. In the project and data collection phase were used a documentary and bibliographic research. The instrument of data collection was developed based on the indicators of the CAPES evaluation system. It was developed and applied to the coordinators of graduate programs in Production Engineering, using a semi-structured questionnaire with open and closed questions. For collected data was realized an integrated analysis of the reports of the Engineering III and the replied questionnaires by coordinators, as a18.4% of the sampled population. As result there has been a need for a revision in the higher weights assigned to certain indicators, for example, the production of papers in journals and consequently the weight of scores for other productions techniques, both the importance of using more than one evaluation factor beyond the Qualis, as cited by respondents, the impact factor of each journal, as well as the need to include more indicators that are able to evaluate graduate programs.